Sosialisasi Teknik Penanaman Tanaman Pekarangan dalam Pot (TaRaPot) di Desa Tengguli, Jepara - Nada Radilla; Moh. Faris Nofianto; Ade Wachjar (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
Tengguli Village is one of the villages in Bangsri District, Jepara, where most of the land use is used for buildings or yards. Empty land or land can be used as productive activities that can improve the family's economy, improve community food security, and utilize superior local products of the village. Utilization of vacant land or yard needs to be developed in Tengguli Village with the socialization of planting techniques for potting plants (TaRaPot). This activity aims to increase public knowledge about various types of plants in pots and their planting techniques, and utilize garden plants to meet kitchen needs without having to buy. The method used is a participatory method where the community is placed as a subject in every activity, starting from planning, implementation, and evaluation. The program begins with the provision of materials about garden plants and their benefits in daily life, then directly practices planting garden plants in pots by the demonstration method. This program runs with very high enthusiasm from the participants. The implementation of this program can increase community knowledge regarding the optimal use of yard and can help food security in daily life. Keywords: Tengguli Village, Empty land, Participatory methods, Yard, Tarapot